Protein expression profiles that underpin the preventive and therapeutic potential of Moringa oleifera Lam against azoxymethane and dextran sodium sulfate-induced mouse colon carcinogenesis - Phannasil, Phatchariya (Oncol Lett, 2020)
Previous studies in a mouse model have indicated the anticancer potential of boiled Moringa oleifera pod (bMO)-supplemented diets; however, its molecular mechanisms are still unclear. Therefore, the present study aimed to explore the protein expression profiles responsible for the suppressive effect of bMO supplementation on azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced mouse colon carcinogenesis. Analysis by gel electrophoresis and liquid chromatography-tandem mass spectrophotometry demonstrated that there were 125 proteins that were differentially expressed in mouse colon tissues between 14 experimental groups of mice. The differentially expressed proteins are involved in various biological processes, such as signal transduction, metabolism, transcription and translation. Venn diagram analysis of the differentially expressed proteins was performed in six selected mouse groups, including negative control, positive control mice induced by AOM/DSS, the AOM/DSS groups receiving preventive or therapeutic bMO diets and their bMO-supplemented control groups. This analysis identified 7 proteins; 60S acidic ribosomal protein P1 (Rplp1), fragile X mental retardation, cystatin 9, round spermatids protein, zinc finger protein 638, protein phosphatase 2C (Ppm1g) and unnamed protein product as being potentially associated with the preventive and therapeutic effects of bMO in AOM/DSS-induced mouse colon cancer. Analysis based on the search tool for interactions of chemicals (STITCH) database predicted that Rplp1 interacted with the apoptotic and inflammatory pathways, whereas Ppm1g was associated only with inflammatory networks. This proteomic analysis revealed candidate proteins that are responsible for the effects of bMO supplementation, potentially by regulating apoptotic and inflammatory signaling networks in colorectal cancer prevention and therapy.